2016
DOI: 10.5535/arm.2016.40.3.432
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of Dysphagia in Severe Traumatic Brain Injury Patients: A Comparison With Stroke Patients

Abstract: ObjectiveTo compare the swallowing characteristics of dysphagic patients with traumatic brain injury (TBI) with those of dysphagic stroke patients.MethodsForty-one patients with TBI were selected from medical records (between December 2004 to March 2013) and matched to patients with stroke (n=41) based on age, sex, and disease duration. Patients' swallowing characteristics were analyzed retrospectively using a videofluoroscopic swallowing study (VFSS) and compared between both groups. Following thorough review… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 34 publications
(32 citation statements)
references
References 21 publications
0
29
0
3
Order By: Relevance
“…Starmer et al (2015) reported that patients with post-radiated submental muscles who penetrated and aspirated also had decreased dLVC (Starmer et al, 2015). These, and many other studies that link disordered LVC to aspiration, highlight the complexity of LVC mechanics and its pathophysiology (Lee et al, 2016; Power et al, 2009; Power et al, 2007). To our knowledge, the vLVC swallowing maneuver is the only treatment option that requires individuals to focus on modifying LVC gestures alone during a swallow.…”
Section: Discussionmentioning
confidence: 76%
“…Starmer et al (2015) reported that patients with post-radiated submental muscles who penetrated and aspirated also had decreased dLVC (Starmer et al, 2015). These, and many other studies that link disordered LVC to aspiration, highlight the complexity of LVC mechanics and its pathophysiology (Lee et al, 2016; Power et al, 2009; Power et al, 2007). To our knowledge, the vLVC swallowing maneuver is the only treatment option that requires individuals to focus on modifying LVC gestures alone during a swallow.…”
Section: Discussionmentioning
confidence: 76%
“…What does an eating and swallowing rehabilitation visit mean for the provision of long-term care for your family member at home? study participants were: (1) the cause of dysphagia was stroke or TBI (these were unified into a single disease within 1 focus group interview); (2) >1 year had passed from the initiation of EN via a PEG tube for the patient; (3) the score of the modified Rankin Scale (mRS), a physical assessment tool of disability due to stroke, was 4 or 5 20 ; (4) the main nutrition supply was via a feeding tube; (5) the patient retained the ability to communicate, including via nonverbal communication; (6) the patient lived in a home with a family caregiver; and (7) the patient had received periodic swallowing rehabilitation visits for >1 year. Swallowing ability was estimated by the Functional Oral Intake Scale (FOIS), with a low score indicating severe dysphagia (range: 1-7).…”
Section: Methodsmentioning
confidence: 99%
“…The reported prevalence of dysphagia at 6 months after onset is 50% in stroke survivors . The prevalence of dysphagia with TBI in the chronic phase is unknown; however, the characteristics and severity of dysphagia between stroke patients and TBI patients are not significantly different …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Dysphagia also may result from traumatic or nontraumatic brain injury, depending on the area and extent of injury. 6 Spinal cord injury can cause dysphagia as well. [7][8][9] Neurodegenerative diseases and neuromuscular diseases, including but not limited to Parkinson's disease, multiple sclerosis, amyotrophic lateral sclerosis, muscular dystrophies, poliomyelitis, myasthenia gravis, and dementias, are other causes of dysphagia.…”
Section: Causesmentioning
confidence: 99%